Views about mixed methods research from counselling and psychotherapy research students and supervisors - McBeath, Alistair; Bager-Charleson, Sofie; Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2023)
How do students and supervisors who are actively involved in the process of research view and experience mixed methods research? This study explores views held by counselling and psychotherapy research students and supervisors around mixed methods research, based on a survey reaching 125 respondents. The survey generated both quantitative data from an online survey and qualitative data from free text comments and a story completion approach. Knowledge about mixed methods research was not widespread (59%) although there was a majority view (81%) that qualitative and quantitative research methods could be meaningfully combined. There was a clear majority view (87%) that it is important for researchers in counselling and psychotherapy to have a working knowledge of mixed methods research. Out of 49 story stem replies, 46 were in support of mixed methods.  A discussion explores the implications of these findings for training and supervision.